Mechanical Proofreading: A General Mechanism to Enhance the Fidelity of Information Transfer Between Cells - Brockman, Joshua M.; Salaita, Khalid (Frontiers in Physics, 2019)
The cells and receptors of the immune system are mechanically active. Single molecule force spectroscopy, traction force microscopy, and molecular tension probe measurements all point to the importance of piconewton (pN) molecular forces in immune function. For example, forces enhance the ability of a T cell to discriminate between nearly identical antigens. The role of molecular forces at these critical immune recognition junctions is puzzling because mechanical forces generally facilitate bond dissociation, potentially increasing the difficulty for a receptor to recognize its cognate antigen. The advantage molecular forces confer in the process of immune recognition is not clear. Why would cells expend energy to exert force on the critical, but tenuous bonds that mediate immune surveillance? Do molecular forces provide some advantage to the immune system? The premise of this review is that molecular forces provide a specificity advantage to immune cells. Inspired by the recent discovery that receptor forces regulate immune signaling in T cells and B cells, we dub this notion “mechanical proofreading,” akin to more classic kinetic proofreading models. During the process of mechanical proofreading, cells exert pN receptor forces on receptor-ligand interactions, deliberately increasing the energy cost of the immune recognition process in exchange for increased specificity of signaling. Here, we review the role of molecular forces in the immune system and suggest how these forces may facilitate mechanical proofreading to increase the specificity of the immune response.